2022
DOI: 10.3389/fpsyg.2022.850842
|View full text |Cite
|
Sign up to set email alerts
|

Innovation to Immune: Empirical Evidence From COVID-19 Focused Enterprise Surveys

Abstract: The recent COVID-19 crisis caught many by surprise. Yet some firms were better prepared to weather the downturn than others. Using a comprehensive data set that observes over 15,000 firms in 27 countries, including several developing countries, shortly before and after the pandemic, we document that pre-crisis innovation affected firm’s survival odds and performance thereafter. The results show that innovative firms are less likely to close and perform better than non-innovators during the pandemic crisis. Inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
(100 reference statements)
1
2
0
Order By: Relevance
“…In addition, the findings presented in column 2 demonstrate that research and development has a significant influence, both positively and negatively, on innovation. These findings demonstrate that spending on R&D prior to the WTO had a direct impact on patenting after the PNTR period, which is consistent with [18,39,57].…”
Section: Notesupporting
confidence: 76%
See 1 more Smart Citation
“…In addition, the findings presented in column 2 demonstrate that research and development has a significant influence, both positively and negatively, on innovation. These findings demonstrate that spending on R&D prior to the WTO had a direct impact on patenting after the PNTR period, which is consistent with [18,39,57].…”
Section: Notesupporting
confidence: 76%
“…Moreover, adaptation modulates the relationship between innovation and survivability. Innovative firms are more likely to create new products, remote work arrangements, and increase delivery, pivoting, and online activity during the pandemic crisis than non-innovators [57].…”
Section: Sustainable Developmentmentioning
confidence: 99%
“…Other factors influencing the ability of SMEs to survive and cope with the coronacrisis include employee and customer satisfaction in the changing situations. (Khan et al 2022;Fasth et al 2022;Thekkoote 2023). A study by Dyduch et al (2021) showed that the alignment of the organisation's internal and external environments had a mitigating effect on the decline in business performance during the coronacrisis.…”
Section: Literature Reviewmentioning
confidence: 99%